Operational decision making in sports: What determines whether a volleyball player goes for a set or a dig? - Ntolopoulou, M.; Bootsma, R. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Often a particular situation offers multiple operational possibilities. For instance, a volleyball player may choose to play a ball using a set or a dig technique. In this research project we seek to identify the constraints harnessing the operational choices made by expert players. To this end, we confront them with a range of situations in order to determine to what extent the choices made are systematically related to the situations encountered, as is predicted by an affordance-based account of behaviour (Fajen, Riley, & Turvey, 2008). After having identified the particular constraints (e.g., time available, distance to covered) that separate the solutions adopted, we examine the relations between the visual information used to guide the movement toward the point of interception (Michaels & Oudejans, 1992) and the players` action capabilities in order to pinpoint the informational support for operational decisions making. Method: Tested separately, six top-level French volleyball players attempted to play machine-launched balls into a circular goal positioned at the passer`s position near the net. Each trial had the player start from one of 5 different initial positions (between 2 and 8 m from the net) and play one a 4 different balls trajectories (varying in landing position for a constant flight time of 1.9 s). Each player performed 80 trials (5 initial positions x 4 ball trajectories x 4 repetitions). For each trial, the action mode chosen (set or dig) was recorded. When a given ball trajectory gave rise to a change in action mode as a function of the player`s initial position, motion of the ball and player was analysed from video recordings using the SIMI motion system operating at 25Hz. Data processing is currently underway